تحليل العلاقة بين التنمية الاقتصادية والسياسة النقدية وفق آليات التعافي - الزركوشي، علياء حسين خلف; حسن، ضياء عبدالرزاق (جامعة تكريت - كلية الإدارة والاقتصاد, 2023)
للسياسة النقدية والائتمانية دورا مهما في تحقيق الإصلاح الاقتصادي عبر الضوابط والتعليمات المنبثقة في ضوء الأهداف الاقتصادية وبواسطة الأدوات النقدية لتحقيق الاستقرار الاقتصادي عبر تخفيض معدلات الأسعار (التضخم) واستقرار سعر الصرف، وإعادة بناء الاحتياطيات الأجنبية للبنك المركزي والحفاظ على نظام مالي مستقر قائم على بيئة تنافسية، وتوفير حاضنة أساسية لعملية الانطلاق التنموي في العراق وبلوغ أهداف الاستدامة الفاعلة، ويهدف البحث إلى تحديد العلاقة التي تربط بين السياسة النقدية والتنمية الاقتصادية ومعرفة مدى استجابة المؤشرات الاقتصادية للسياسة النقدية، من خلال قياس وتحليل تحقيق التنمية الاقتصادية بالمفهوم الحديث عبر آليات الإصلاح النقدي باستعمال نموذج ARDL، ومن أهم النتائج التي تم التوصل إليها هي تأثير السياسة النقدية على التنمية الاقتصادية يتوقف على مدى فعاليتها باعتمادها على عناصر موضوعية في ضخ الكتلة النقدية كمراعاة حجم الإنتاج الحقيقي والتحكم في معدلات التضخم، أما أهم المقترحات ضرورة استكمال إصلاح المنظومة المصرفية والمالية ومتابعة تطوير كل من السوقين النقدي والمالي بوصفهم أحد أهم ركائز تطبيق سياسة نقدية فاعلة مؤثرة في التنمية. Monetary and credit policy plays an important role in achieving economic reform through the controls and instructions emanating in light of economic goals and by monetary tools to achieve economic stability by reducing price rates (inflation) and the stability of the exchange rate, He rebuilt the foreign reserves of the central bank, maintained a stable financial system based on a competitive environment, provided a basic incubator for the development launch process in Iraq and reached effective sustainability goals, The research aims to determine the relationship between monetary policy and economic development and to know the extent to which economic indicators respond to monetary policy, By measuring and analyzing the achievement of economic development in the modern sense through monetary reform mechanisms using the ARDL model, Among the most important results reached is the impact of monetary policy on economic development, depending on its effectiveness by relying on objective elements in pumping cash mass, such as taking into account the volume of real production and controlling inflation rates,,, As for the most important proposals, it is necessary to complete the reform of the banking and financial system and follow up the development of both the monetary and financial markets as one of the most important pillars of implementing an effective monetary policy that affects development.
Keywords: السياسات النقدية -- الإصلاح الاقتصادي -- آليات التعافي -- العراق